2001
DOI: 10.1353/psc.2001.0029
|View full text |Cite
|
Sign up to set email alerts
|

Cruise Ships and Prison Camps: Reflections from the Russian Far East on Museums and the Crafting of History

Abstract: In formerly socialist societies the state has dominated sites like museums viewed as critical for producing a national past, but in the case of the Russian Federation these same institutions often are being utilized now to critically examine the past. For many in the emerging market economy of the Russian Federation, formerly state-dominated sites like museums have become important economic resources as well as new sites for representing shifting concepts of history. In this article I examine the museum as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Related to violence, the politics of rewriting history, acquiring knowledge, and reconfiguring identity have concerned many anthropologists (Bloch 2000(Bloch , 2001Bloch & Kendall 2004;Borneman 2004;Boyer 2005;Empson 2007;Grant 1995;Ssorin-Chaikov 2003). Kaplonski's (2004) study of social memory in Mongolia in the midst of shifting and controversial identity formation demonstrated that memory is based on the identities of historical heroes rather than on spaces or places.…”
Section: Sites Of Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Related to violence, the politics of rewriting history, acquiring knowledge, and reconfiguring identity have concerned many anthropologists (Bloch 2000(Bloch , 2001Bloch & Kendall 2004;Borneman 2004;Boyer 2005;Empson 2007;Grant 1995;Ssorin-Chaikov 2003). Kaplonski's (2004) study of social memory in Mongolia in the midst of shifting and controversial identity formation demonstrated that memory is based on the identities of historical heroes rather than on spaces or places.…”
Section: Sites Of Culturementioning
confidence: 99%
“…The cultural developments among the colonized people of the former Russian Empire differ from those among the people from the European part of Russia. The colonial past of the former is embedded in ambiguous resistance to the Soviet past, which is mediated through rituals, folk medicine, and attitudes toward the state (Balzer 1996(Balzer , 1999(Balzer , 2001(Balzer , 2005Bloch 2001;Rethman 2001). Sabloff (2001) argued that Mongolia has its own concept of democracy from its distant history.…”
Section: Sites Of Culturementioning
confidence: 99%